(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Improving the effectiveness of teaching history using innovative technologies. The article discusses the importance of facilitating teaching, the importance of using a variety of methods and techniques to engage students in learning, game technology as one of the most innovative learning technologies, and its effectiveness.